"Eruptive Lentiginosis" in a Patient With Vitiligo and Inflammatory Bowel Disease Treated With Azathioprine. (February 2016) - Ramos-Rodríguez, Claudia; Murillo-Lázaro, Cristina; Mendoza-Chaparro, Carlos
Abstract : Abstract: Multiple lentiginosis are seen in many multisystemic diseases and during the course of many treatment schemes in the area of application of topical substances, PUVA, or more disseminated reactions in the case of systemic drugs. We report a case of a 67-year-old man with multiple comorbidities including vitiligo, and a recent diagnosis of inflammatory bowel disease, who developed millimeter-size, circular, brown macules in photoexposed areas both affected and not affected by vitiligo while was taken azathioprine, which disappeared after drug withdrawal. Biopsy showed groups of apoptotic keratinocytes, basal hyperpigmentation, and slight dermal inflammation. The authors describe "eruptive lentiginosis" as an adverse event of azathioprine not previously described in the literature.